An early warning system for currency crises in emerging countries - Lutfa Tilat Ferdous; Khnd Md Mostafa Kamal; Amirul Ahsan; Nhung Hong Thuy Hoang; Munshi Samaduzzaman (Journal of Risk and Financial Management, 2022)
In this study we develop an early warning system (EWS) to forecast currency crises in emerging countries in Asia and Latin America, using logit regression on monthly data from 1992 to 2011. We found that macroeconomic and institutional variables are valuable indicators for forecasting crises. Our results show that a low level of export growth, current account surplus/GDP, GDP growth, a high level of real exchange rate growth, import growth, and short-term debt/reserves can explain the advent of a possible currency crisis. We found that a poor law and order scenario and high external conflict can lead to a currency crisis. Additional findings include high government stability and the absence of internal conflict, which contribute to an absence of democracy, ultimately leading to a currency crisis. The policy-makers can consider taking the effective pre-emptive actions to prevent the currency crises occurring in the future.
Keywords: 650; currency crisis; early warning system; emerging countries; logit model